2016
DOI: 10.1177/1071100716642845
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Operative Factors Related to Successful Revision Arthrodesis in the Foot and Ankle

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 33 publications
0
21
1
Order By: Relevance
“…The importance of a sufficient volume of graft material in achieving foot or ankle fusion was previously described [34,35]. That study demonstrated a decrease in fusion rate with increased volume of graft material.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The importance of a sufficient volume of graft material in achieving foot or ankle fusion was previously described [34,35]. That study demonstrated a decrease in fusion rate with increased volume of graft material.…”
Section: Discussionmentioning
confidence: 85%
“…Since both T EV or T EL groups utilized the same window, this does not affect the comparative conclusions. In addition, this 4-month window is relatively narrow compared to recently published retrospective studies that utilized windows ranging from 16-48 months [34,36,37]. Lastly, retrospective studies have the potential for selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…The increased utility of operative intervention for complex limb salvage in conditions such as Charcot neuroarthropathy has resulted in an awareness of the intricacies of bone consolidation, despite the availability and use of improved fixation constructs. The foot and ankle literature report nonunion rates in arthrodesis as high as 41% in high-risk populations, including those with Charcot neuroarthropathy (1,2). As such, construct augmentation with grafting material is an area of research that warrants attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, non-union is observed in 4.9% of the cases treated for bone fracture [1]. In 23% of ankle arthrodesis cases, for example, non-unions persist, requiring multiple invasive procedures and causing prolonged immobilization and even permanent morbidity [2]. It is therefore important to develop bone substitutes that stimulate bone tissue regeneration and help in overcoming bony non-unions.…”
Section: Introductionmentioning
confidence: 99%